Exchange Rate Pass-through into Prices in Tunisia and Morocco (Global Journal of Management and Business Research, 2012)
This paper examines the degree of Exchange Rate Pass-Through to prices in Tunisia and Morocco, using the two recent methods developed by Edwards (2006) and Gerlach and Gerlach-Kristen (2006). Based on quarterly and annual data from 1980 to 2010, our results show that, whatever the method used, the nominal exchange rate does not play the role of a shock absorber mechanism in these two countries.
Keywords: Pass-through; shock absorber; monetary policy; Tunisia; Morocco